Impactos econômicos globais da redução das emissões de gases de efeito estufa - Silvestrini, Murilo Mazzotti (Universidade Federal de São Carlos, 2018)
The purpose of this work is to simulate reductions in global greenhouse gas emissions (GHG) to analyze the behavior of emissions and gross production value (GVP) of 40 countries considering the global emission mitigation target, identifying those that present greater economic impact. The methodology of this work is based on the use of Linear Programming and Input-Output in the Multi Regional matrix with GHG emissions, and the data used are from the WIOD tables which represents 40 countries composed by 35 sectors for the year 2009. Three different scenarios were modeled: the pessimistic scenario, the moderate scenario and the optimistic scenario, with reduction of 10%, 30% and 50% of the global GHG emissions, respectively. The results showed the greatest emission reductions in China, India, Russia and Brazil, which also showed the greatest decrease in VBP. The United States and Japan, despite of presenting a high percentage of emission reductions, especially in the optimistic scenario, had a lower economic impact due to their economic structure. European countries, such as Germany, the United Kingdom and France, showed little reduction in emissions and VBP. Furthermore, the scenarios modified the overall composition of emissions and VBP, with the share of GHG emissions increasing in European countries, in addition to the increase of their participation in global VBP. The conclusion is that the reduction of emissions in the face of a global GHG mitigation goal is greater in the most emission-intensive countries, causing the greatest economic impact, mainly due to the production structure of the economic sectors based on higher emission technologies.
Global economic impacts of the reduction of greenhouse gas emissions
Keywords: Redução de gases do efeito estufa; Acordos internacionais; Matriz Multi-Regional de Insumo-Produto; Programação Linear; Greenhouse gas mitigation; International agreements; Input-Output; Linear Programming; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INTERNACIONAL; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA